Effects of Teachers' Professional Knowledge and Their Use of Three-Dimensional Physical Models in Biology Lessons on Students' Achievement - Sonja Förtsch; Christian Förtsch; Lena von Kotzebue; Birgit J. Neuhaus (MDPI AG, 2018)
Using three-dimensional physical models elaborately in their learning, students can develop high-level understanding of models and modeling in science, thereby attaining higher achievement. However, there are in the literature few indications of how teachers should use three-dimensional physical models in instruction and whether teachers’ professional knowledge is a prerequisite for teaching with elaborate use of models. Therefore, our study used a mixed-methods approach to analyze the effects of biology teachers’ domain-specific pedagogical content knowledge (PCK) and content knowledge (CK) on students’ achievement mediated by elaborate model use (ELMO). Our quantitative sample comprised 36 German secondary school teachers whose lessons on the topic of neurobiology were videotaped twice (N = 72 lessons). Teachers completed professional knowledge tests on their PCK and CK. Students’ achievement was measured using pre- and post-knowledge tests. Our qualitative analysis involved five selected teachers according to aspects of ELMO. The results of our study indicated that teachers’ PCK and CK had no direct effect on students’ achievement. However, teachers’ PCK had a significant indirect and positive effect on students’ achievement mediated by ELMO. The findings of our study can provide teachers and researchers examples of how to implement biology instruction with elaborate use of three-dimensional physical models.